A Climatology of Merged Daytime Planetary Boundary Layer Height Over China From Radiosonde Measurements. Issue 12 (17th June 2022) - Zhang, Jian; Guo, Jianping; Li, Jian; Zhang, Shaodong; Tong, Bing; Shao, Jia; Li, Haiyan; Zhang, Yehui; Cao, Lijuan; Zhai, Panmao; Xu, Xiaofeng; Wang, Minghuai
Abstract: The planetary boundary layer is crucial for the turbulence mixing and exchange of heat flux, momentum, and atmospheric pollutants between the atmosphere and Earth's surface. Nevertheless, the estimated boundary layer height (BLH) varies greatly by data sources and algorithms. This paper seeks to characterize the convective BLHs from 1‐s radiosonde measurements of China Radiosonde Network (CRN) for the 2012–2020 period at 1400 Beijing time, by using eight well‐known algorithms, wherein the newly established Thorpe method is theoretically fundamental on turbulence analysis and is in remarkable agreement with the parcel and bulk Richardson number methods. BLHs obtained by eight methods, ranging from 1.2 to 2.5 km, strongly vary with methods based on different kinetic or thermodynamic theories. The significant offsets among methods motivate the present study to propose a merged algorithm, to minimize the spread of BLH estimate. The merged BLH contains more physical information than that retrieved from a single method and can significantly lower the uncertainty. The BLH climatology exhibits a spatial pattern of "Southwest‐High Southeast‐Low, " ascending from 0.6 km over southeastern China to 2.3 km over southwestern China, which could be largely attributed to the variations in the integrated surface sensible heat flux, soil moisture, total cloud cover, land cover, synoptic forcing, and terrain‐induced flow. Of interest is that land surface properties could be the major driver for the development of CBL. Also noteworthy is that the smallest BLH is expected under the strongest synoptic forcing condition. Plain Language Summary: The planetary boundary layer (PBL), where the exchanges of heat, moisture, momentum, and mass mainly occur with a variety of physical and chemical processes involved, is the lowest part of the troposphere in direct contact with the ground surface. However, the determination of boundary layer height (BLH) tends to be dramatically influenced by the dataset and methods used. Few studies have been conducted to evaluate the discrepancy of nationwide daytime BLH over China originating from the methods used. In particular, eight well‐known methods, including the novel Thorpe method and seven other traditional methods, are applied to estimate BLHs from high‐resolution soundings from the China Radiosonde Network. However, BLH derived by eight methods vary from approximately 1.2 to 2.5 km, strongly depending on the method. Therefore, to compile a more convincing BLH dataset eight methods are selected and composed as a merged BLH. The climatology of the merged BLH for the period 2012–2020 shows a well‐defined "Southwest‐High Southeast‐Low " pattern, which could be attributed to the diversities in sensible heat flux, soil moisture, land cover, total cloud cover, synoptic forcing, and terrain‐induced flow across China. Key Points: The merged boundary layer height (BLH) is synthesized from eight methods and it carries more planetary boundary layer (PBL) information and can considerably lower the uncertainties The "Southwest‐High Southeast‐Low" pattern of BLH could be attributed to land properties, synoptic forcing, and terrain‐induced flow Under weak synoptic forcing condition the development of convective PBL is more susceptible to the variation of land surface properties